Complex PrEP: the factors requiring consultant-led review of PrEP users. (15th February 2022) - Tittle, Victoria; Dalton, Rebecca; Nugent, Diarmuid; Girometti, Nicolo; Whitlock, Gary; Mcowan, Alan; McCormack, Sheena
Abstract : Introduction: HIV-1 pre-exposure prophylaxis (PrEP) has been available in England since March 2020 on the National Health Service using generic emtricitabine and tenofovir disoproxil. 56 Dean Street (56DS) provided PrEP through (1) additional private care from September 2015, estimated to be providing 11% of England's PrEP in 2019; and (2) the IMPACT trial, as well as monitoring those self-sourcing PrEP. Providing PrEP at scale through a nurse-led service required a safety net for complex individuals. 56DS introduced a consultant-led PrEP outpatient service, the PrEP review clinic, in January 2018 and we report the outcomes of this service. Methods: We present a retrospective case note review of the PrEP review clinic with descriptive outcomes from 26 January 2018 to 20 December 2019. Reason for referral, demographics, PrEP management and PrEP discontinuations were recorded. Results: 13 980 unique users accessed PrEP from 56DS during the two year evaluation period. 220 individuals were seen in the PrEP review clinic. Majority of patients were referred for renal issues (114 of 220, 51.8%), followed by side effects (59 of 220, 26.8%) and comorbidities (38 of 220, 17.2%). Of those with renal issues, 89 (out of 114, 78.1%) users were referred for an abnormal estimated glomerular filtration rate (eGFR). 35 (out of 114, 30.7%) PrEP users had an eGFR between 45 and 59 mL/min/1.73 m 2, of whom 2 (5.7%) discontinued PrEP. Majority of users were advised to stop supplements±switch to event-based dosing (24 of 35, 68.6%). Ten PrEP users were referred with an eGFR between 30 and 44 mL/min/1.73 m 2 ; 4 (40%) stopped or did not start PrEP and 6 (60%) were asked to stop supplements±switch to event-based dosing. Discussion: A small proportion of PrEP users have complex PrEP issues. Methods to manage renal dysfunction with PrEP included stopping supplements and switching to event-based dosing. Those with side effects were managed with an array of options, with only modest effectiveness. Other PrEP options are needed to support those with toxicities or intolerances.